Thermal conductivity variations with composition of gelatin-silica aerogel-sodium dodecyl sulfate with functionalized multi-walled carbon nanotube doping in their composites - Mahesh, Sachithanadam (2015)
Silica aerogels are very light, highly porous nanomaterial with large internal surface area possessing excellent thermal insulation that may get affected when the binders and additives used in aggregation. This paper discusses the variations in thermal conductivity of a binder-treated gelatin silica aerogel-sodium dodecyl sulfate (GSA-SDS) composite blocks doped with COOH group functionalized multi-walled carbon nanotubes (FMWNT) prepared via freeze drying and frothing methods. The thermal conductivity of GSA-SDS and GSA-SDS/FMWNT composites was evaluated with several mass ratios of the composite mix for 1-D steady-state heat transfer at mean temperature, Tm (300-370K), using Lee’s Disc method. The effects of silica aerogel granule size and mass ratio of FMWNT on the thermal conductivity were investigated. The lowest thermal conductivity achieved for the composite block was 0.016 W/m-K when 0.042 wt% FMWNT was added to gelatin aerogel mass ratio of 0.1:0.9 without SDS. Thermal conductivity predictive models were developed based on the numerous experiments carried out as a function of the aerogel granule size and the mass ratio of constituent materials. The predictive models for composites with FMWNT were validated to approximately 94.3 ± 2.4% accuracy with reduction of 7% in the thermal conductivity when compared with of the GSA composites.